HIV/AIDS and air pollution as emerging cardiovascular risk factors in Cape Town populations : is endothelial function a marker of effect - Everson, Frans Pieter (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.